1999
DOI: 10.1099/0022-1317-80-5-1283
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-induced endocytosis of viral glycoproteins and major histocompatibility complex class I on pseudorabies virus-infected monocytes.

Abstract: Purified porcine monocytes, the natural carrier cells of pseudorabies virus (PrV) in the pig, were inoculated in vitro with PrV. At different time-points post-inoculation (p.i.) (from 7 to 17 h p.i.), the cells were washed and incubated with fluorescein isothiocyanate-labelled porcine PrV-specific polyclonal antibodies (IgG) at 37 mC. At all time-points tested p.i., 1 h of antibody incubation induced passive patching and subsequent internalization of the plasma membrane-anchored viral glycoproteins in approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 27 publications
(13 reference statements)
2
87
2
Order By: Relevance
“…Earlier, we and others have shown that the interaction between PRV or HSV polyclonal serum antibodies and the viral proteins on the cell surface initiates intriguing, cell typedependent redistribution processes of the antibody-antigen complexes (8,10,39). Addition of polyclonal serum immunoglobulin G (IgG) to PRV-infected swine kidney (SK) cells or HSV-infected human embryonic lung fibroblasts (HEL cells) and human larynx epidermoid carcinoma (Hep-2) cells leads to aggregation of the viral cell surface proteins into patches, which subsequently polarize to one side of the cell to form a cap (10,39), sometimes followed by shedding of the caps (10).…”
Section: Pseudorabies Virus (Prv) Is a Swine Alphaherpesvirus That Ismentioning
confidence: 90%
See 3 more Smart Citations
“…Earlier, we and others have shown that the interaction between PRV or HSV polyclonal serum antibodies and the viral proteins on the cell surface initiates intriguing, cell typedependent redistribution processes of the antibody-antigen complexes (8,10,39). Addition of polyclonal serum immunoglobulin G (IgG) to PRV-infected swine kidney (SK) cells or HSV-infected human embryonic lung fibroblasts (HEL cells) and human larynx epidermoid carcinoma (Hep-2) cells leads to aggregation of the viral cell surface proteins into patches, which subsequently polarize to one side of the cell to form a cap (10,39), sometimes followed by shedding of the caps (10).…”
Section: Pseudorabies Virus (Prv) Is a Swine Alphaherpesvirus That Ismentioning
confidence: 90%
“…Addition of polyclonal serum immunoglobulin G (IgG) to PRV-infected swine kidney (SK) cells or HSV-infected human embryonic lung fibroblasts (HEL cells) and human larynx epidermoid carcinoma (Hep-2) cells leads to aggregation of the viral cell surface proteins into patches, which subsequently polarize to one side of the cell to form a cap (10,39), sometimes followed by shedding of the caps (10). In PRV-infected blood monocytes, on the other hand, patches of viral cell surface proteins are rapidly internalized and do not cap (8). The exact function of these processes is not fully understood, although there are strong indications that they may be important for alphaherpesviruses to enhance virus survival in the face of an antibody response.…”
Section: Pseudorabies Virus (Prv) Is a Swine Alphaherpesvirus That Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Such attachment has already been described between PrVinfected monocytes and endothelial cells [67]. PrV-infected monocytes that have been exposed to virus-specific antibodies internalize their viral glycoproteins together with their MHCI molecules, leaving cells that are masked from efficient recognition and elimination by different components of the immune system [11,68]. These immune-masked monocytes have been shown to adhere specifically to endothelial cells by the cellular adhesion molecules wCD11R3 and CD18.…”
Section: Cell-associated Spreadmentioning
confidence: 77%